Courtesy Beyond Stereotypes: Sociological and Legal Sociological Insights into Iranian Society - Arief Fahmi Lubis; Seyed Nawab Mousavi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
This study examines the social realities of Iranian society, often misrepresented in international media that focus on politics, conflict, or conservatism. Using a sociological and humanistic perspective, it highlights everyday practices of courtesy, social norms, and traditions. The taarof ritual a unique form of politeness is discussed as a vivid example of how Iranians foster social harmony, respect guests, and demonstrate solidarity. The article also considers the impact of formal and customary law on social behavior, alongside the interplay between tradition and modernity in urban and rural contexts. Field observations and literature review suggest that Iranian society maintains high levels of courtesy and social cohesion, challenging common stereotypes. This research aims to enrich cross-cultural understanding and provide a more nuanced view of social life in Iran.